2021
DOI: 10.1007/978-3-030-73785-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Coherent Graph Transformations

Abstract: Cellular automata as well as simultaneous assignments in Python can be understood as the parallel application of local rules to a grid or an environment that can be easily represented as an attributed graph. Since the result of such transformations cannot generally be obtained by a sequential application of the involved rules, this situation infringes the standard notion of parallel independence. An algebraic approach with production rules of the form L Ð K Ð I Ñ R is adopted and a condition of parallel cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Another possibility for defining parallel rewriting is to translate to the present framework the notion of parallel coherence that has been devised in order to define algebraic parallel graph transformation (see [4]). In that paper we used production rules of the form L ← K ← I → R that do not require a morphism from K to R. Direct derivations are commuting diagrams…”
Section: Parallel Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility for defining parallel rewriting is to translate to the present framework the notion of parallel coherence that has been devised in order to define algebraic parallel graph transformation (see [4]). In that paper we used production rules of the form L ← K ← I → R that do not require a morphism from K to R. Direct derivations are commuting diagrams…”
Section: Parallel Coherencementioning
confidence: 99%
“…Section 7 is devoted to comparisons with the algebraic notion of parallel coherence from [4]. It is shown that its translation to the present framework, though more general than regularity, is still too restricted to encompass parallel independence.…”
Section: Introductionmentioning
confidence: 99%